Itaconate induces tolerance of Staphylococcus aureus to aminoglycoside antibiotics - Zhao, Runping; Xu, Lei; Chen, Jieyun; Yang, Yanxian; Guo, Xilong; Dai, Min; Tian, Guo-Bao; Qin, Li-Na (Frontiers in Microbiology, 2024)
Staphylococcus aureus (S. aureus) is one of the main pathogens that cause chronic and recurrent infections. Failure of antibiotics to eradicate infections is an important reason for the high mortality rate and contributes to relapse. Treatment failure may be due to antibiotic tolerance. In this study, we found that the immune metabolite itaconate can induce tolerance in both methicillin-resistant and -susceptible S. aureus to aminoglycosides. When S. aureus was exposed to itaconate, its growth slowed down and displayed transcriptomic and metabolomic alterations associated with decreased energy metabolism, including the tricarboxylate cycle, glycolysis, pyruvate metabolism, and arginine biosynthesis. These changes are associated with aminoglycosides tolerance. This work highlighted the role of immune signaling metabolites in bacterial antibiotic tolerance and suggested new strategies to improve antibiotic treatment for by modulating the host immune response and stimulating the metabolism of bacteria.